ANALYSIS AND INTERPRETATION OF TIME-LAPSE MICORGRAVITY DATA CASE STUDY IN KOTA LAMA SEMARANG TOURISM AREA - Supriyadi, Supriyadi; Khumaedi, Khumaedi; Sugiyanto, Sugiyanto (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
A time-lapse microgravity survey has been carried out in the Kota Lama (Semarang, Indonesia) tourism area. The survey in question is to measure gravity at the same point repeatedly with a specific time interval, in this case, conducted in January 2019 and July 2019. Measuring gravity is carried out at as many as 75 points that are spread evenly at the survey location. The instrument used is a Scintrex CG5 type gravimeter and GPS to determine the latitude and the longitude of each measuring point. The measurement results after being corrected, namely the Apungan and the Appeal correction, obtained the observational gravity (gob) in the January 2019 period showing that a minimum of 978118.44 mGal and a maximum gravity of 978118.88 mGal, while the minimum gravity measurement value in July 2019 showed a minimum of 978118.62 mGal and a maximum of 978118.88 mGal. Changes in the value (anomaly) gravity during the time interval, there are two possibilities, positive (0.02 to 0.29 mGal) and negative (-0.11 to -0.01 mGal). Both of these anomaly prices, if they are modeled, an anomaly source will be obtained, which is a positive anomaly caused by subsidence and a negative caused by changes in subsurface density related to dynamics (decrease or increase) of groundwater level.